2020
DOI: 10.3390/su12083386
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Activism and Big Data: Building Green Social Capital in China

Abstract: The rapid development of information and communication technologies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Green social capital is the value of the interaction or relationship between the employees of organization and the public for the success of organizations and environmental protection. Green social refers to establish social networks and pro-environmental social norms to address the local pollution problems (Xu and Zhang, 2020). Green social capital plays a very important contribution to maintain the values of the organization, environment and to measure the level of social capital within the organization.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Green social capital is the value of the interaction or relationship between the employees of organization and the public for the success of organizations and environmental protection. Green social refers to establish social networks and pro-environmental social norms to address the local pollution problems (Xu and Zhang, 2020). Green social capital plays a very important contribution to maintain the values of the organization, environment and to measure the level of social capital within the organization.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In order to enjoy the benefits gained from green social capital the entire group in the organization should work together to maintain a good relationship with colleagues and society. Green social capital has a positive impact to governess the organization (Xu and Zhang, 2020), environmental performance and innovation (Yadiati, 2019; Delgado-Verde et al ., 2014). However Hesniati and Erlen (2021) found that social capital appeared as an insignificant predictor to enhance the performance in SMEs.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…They have been early adopters of the Internet and active users of social media [ 3 ]. Most notably, Chinese ENGOs have recently begun to apply large numbers of data to improve public participation, leading to the creation of green social capital in China [ 39 ]. Regarding organizational function, ENGOs in China can be divided into three types: (1) solution-focused ENGOs that aim to implement on-the-ground projects and programs to help address a specific environmental issue; (2) service-focused ENGOs that seek to engage people with nature and cultivate environmental literacy and stewardship; and (3) supportive ENGOs that provide funding, knowledge, expertise, ideas, and other resources to promote environmental protection [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%